Q-Squared : Star Trek: The Next Generation - Peter David; Paramount Pictures (U.S.A Pocket Books, 1994)
Q, a mysterious, omnipotent being, once again wreaks havoc on the Enterprise when he returns to challenge his archenemy Trelane, another being from his continuum, and their confrontation could spell the ultimate disaster for Captain Jean-Luc Picard.
Keywords: Science Fiction, Fantasy; Science Fiction -- Science Fiction; Fantasy -- Fantasy